Influence of stirring speed on microstructure and wear morphology of SiCp-6061Al composite - Adebisi, Adetayo Abdulmumin; Maleque, Md. Abdul; Ndaliman, Mohammed Baba (International Journal of Engineering Materials and Manufacture, 2016)
The aim of this study is to investigate the influence of stirring speed on stir casting synthesis of 15 wt% silicon carbide particle reinforced aluminium alloy (SiCp-6061 Al) composite. The composite samples were produced at different stirring speed of 300, 500 and 700 rpm. However, the processing temperature and time are maintained at 800 °C and 180 secs processing condition. Dry reciprocating wear test is conducted using a ball on disc wear tester at a constant operating condition of 50N load, 10Hz frequency for 30 mins on the samples. The influence of stirring speed on the microstructure and wear morphology is examined using scanning electron microscope (SEM). The result reveals that the stirring speed influenced the processing condition including the microstructure and wear topography. Composite processed at 500 rpm attained homogeneity of the SiCp phase as observed from the microstructure. The worn surface experiences a relatively smooth mild wear without formation of cracks, porosity and craters. However, at 300 rpm the composite experiences micro cracks with formation of abrasive grooves due to insufficient distribution of the SiCp phase. Moreover, at 700 rpm high speed vortex formation is observed due to vigorous stirring which entraps gases and develops into large porosity, cracks and deep craters. This study establishes that stirring speed has a significant effect on the processing condition as well as the wear morphology of SiCp-Al6061 composite developed using stir casting technique.